PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MENGGUNAKAN MODEL PROBLEM-BASED LEARNING - Hamimah Hamimah; Ary Kiswanto Kenedi; Zuryanty Zuryanty; Nelliarti Nelliarti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by the learning conducted by the teacher that does not involve students in real problems so that the critical thinking ability of elementary school students in learning social science is low. The purpose of this study was to improve the critical thinking skills of elementary school students using a model of problem-based learning in social studies learning. This research was a classroom action research. The study was conducted on students in the 4th grade at SDN 26 Singkarak with a total of 30 students. These results addressed an increase in students' critical thinking skills from an average score of the initial ability of 65.79, cycle 1 got an average score of 73.87 and increased in cycle 2 with an average score of 81.23. The results showed an increase in the critical thinking skills of elementary school students using a problem-based learning model. This research can be concluded that using problem-based learning can improve the critical thinking skills of elementary school students. This research implies that it can be used as a reference for improving the critical thinking skills of elementary school students.